Effects of gravity on blood flow in the aortic arch - Low, Daryl Wei Hui (2014)
Computational Fluid Dynamics (CFD) analysis of blood flow throughout the body has been carried out extensively since it was started. This analysis has been at the center of many researches that study the effects of certain forces on the body. It could be used to study aneurysms and the effects on the brain. Or it has been used to study the causes of stroke and it has been used to study the effects of gravitational forces (G-forces) on the body. This paper aims to show users that the effect of gravitational forces will cause blood pressure to decrease as the external gravity is increased. The findings of this paper will corroborate past papers that have studied the effects of Gravitational Induced Loss of Consciousness (G-LOC). The paper will identify the different effects of the effects of various levels of gravitational forces that are acting on the system. The simulation will be carried out on the model of an Aortic Arch, which is part of the major artery coming from the heart. As blood flow is generally laminar, there are regions where blood flow can be considered to be turbulent. This paper will aim to show the difference on the effects of the external forces on the aortic arch based on a laminar flow as well as a turbulent flow. The CFD simulations were done using CD-Adapco®’s STAR-CCM+©.